2023
DOI: 10.33438/ijdshs.1197978
|View full text |Cite
|
Sign up to set email alerts
|

The Physical and Mental Health Benefits of Lifestyle Sports for Disabled People: A Scoping Review

Abstract: Background There is growing evidence to suggest the physical and mental health benefits of lifestyle sports (LS) in disabled people. However, disabled people are less likely to participate in sports than those without disabilities and the evidence base is sporadic. Objectives This scoping review explores the range and quality of the evidence base to determine what, if any, physical and mental health benefits are attached to disabled people participating in lifestyle spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
0
0
0
Order By: Relevance
“…Although this study demonstrated gender differences in several outcomes, particularly for the immediate benefits of surf and hike therapies, it is important to emphasize the lack of gender differences in many outcomes, especially regarding long-term benefits. This may speak to the psychological benefits of surf and hike therapies across a variety of different populations [63,64], including those with different psychological conditions [65][66][67]. These findings point to the global and transdiagnostic benefits of surf and hike therapies; these interventions may elicit broad psychological benefits that are not specific to a particular symptom, condition, or group.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study demonstrated gender differences in several outcomes, particularly for the immediate benefits of surf and hike therapies, it is important to emphasize the lack of gender differences in many outcomes, especially regarding long-term benefits. This may speak to the psychological benefits of surf and hike therapies across a variety of different populations [63,64], including those with different psychological conditions [65][66][67]. These findings point to the global and transdiagnostic benefits of surf and hike therapies; these interventions may elicit broad psychological benefits that are not specific to a particular symptom, condition, or group.…”
Section: Discussionmentioning
confidence: 99%